Response surface methodology applied to the evaluation of the SO 2 sorption process in two Brazilian limestones - Mortari, Daniela A.; Ávila, Ivonete [UNESP]; Crnkovic, Paula M. [UNESP] (American Chemical Society (ACS), 2013)
This paper proposes a response surface methodology to evaluate the influence of the particle size and temperature as variables and their interaction on the sulfation process using two Brazilian limestones, a calcite (ICB) and a dolomite (DP). Experiments were performed according to an experimental design [central composite rotatable design (CCRD)] carried out on a thermogravimetric balance and a nitrogen adsorption porosimeter. In the SO 2 sorption process, DP was shown to be more efficient than ICB. The best results for both limestones in relation to conversion and Brunauer-Emmett-Teller (BET) surface area were obtained under central point conditions (545 μm and 850 C for DP and 274 μm and 815 C for ICB). The optimal values for conversion were 52% for DP and 37% for ICB. For BET surface area, the optimal values were 35 m2 g-1 for DP and 45 m2 g-1 for ICB. A relationship between conversion and pore size distribution has been established. The experiments that showed higher conversions also exhibited more pores in the region between 20 and 150 Å and larger BET surface area, indicating that the amount of smaller pores may be an important factor in the reactivity of limestones. © 2013 American Chemical Society.
Keywords: BET surface area; Brunauer-emmett-teller surface areas; Central composite rotatable design; Nitrogen adsorption; Response surface methodology; Sorption process; Sulfation process; Thermo-gravimetric; Experiments; Gas adsorption; Optimal systems; Sulfur dioxide; Surface properties; Limestone